The balanced scorecard : translating strategy into action - Kaplan, Robert S.; Norton, David P. (Boston, Mass. : Harvard Business School Press, 1996)
The balanced Scorecard provides the management system for companies to invest in the long term- in customers, in employees, in new product development, and in systems - rather than managing the bottom line to pump up short-term earnings. The authors also reveal how to use the Balanced Scorecard as a robust learning system for testing, gaining feedback on, and updating the organization's strategy and walked through the steps that managers in any company can use to build their own Balanced Scorecard.
Includes index.
Includes bibliographic references
rua 30/04/13
Loans
Keywords: Strategic planning; Industrial productivity; Organizational effectiveness